Influence of glacier type on bloom phenology in two Southwest Greenland fjords. (5th May 2023) - Stuart-Lee, A.E.; Mortensen, J.; Juul-Pedersen, T.; Middelburg, J.J.; Soetaert, K.; Hopwood, M.J.; Engel, A.; Meire, L.
Abstract: Along Greenland's coastline, the magnitude and timing of primary production in fjords is influenced by meltwater release from marine-terminating glaciers. How local ecosystems will adapt as these glaciers retreat onto land, forcing fundamental changes in hydrography, remains an open question. To further our understanding of this transition, we examine how marine- and land-terminating glaciers respectively influence fjord bloom phenology. Between spring and autumn 2019, we conducted along-fjord transects of hydrographic variables, biogeochemical properties and pico- and nanophytoplankton counts to illustrate the contrasting seasonal bloom dynamics in the fjords Nuup Kangerlua and Ameralik. These fjords are in the same climatic region of west Greenland but influenced by different glacial structures. Nuup Kangerlua, a predominantly marine-terminating system, was differentiated by its sustained second summer bloom and high Chl a fluorescence in summer and autumn. In Ameralik, influenced by a land-terminating glacier, we found higher abundances of pico- and nanophytoplankton, and high cyanobacteria growth in autumn. The summer bloom in Nuup Kangerlua is known to be coincident with subglacial freshwater discharge sustaining renewed nutrient supply to the fjord. We observe here that the intermediate baroclinic circulation, which creates an inflow at subsurface depths, also plays an important role in increasing nutrient availability at shallower depths and potentially explains the distribution of primary producers. Our observations suggest that the retreat of marine-terminating glaciers onto land, with consequent increases in surface water temperature and stratification, and reduced light availability, may alter the magnitude, composition, and distribution of summer productivity. Highlights: Higher representation of picophytoplankton in land-terminating glacier fjord. Smaller phytoplankton cells associated with glacial retreat. Intermediate baroclinic circulation influences phytoplankton distribution. Glacial retreat likely to have major implications for summer productivity.